2020
DOI: 10.1016/j.agee.2019.106810
|View full text |Cite
|
Sign up to set email alerts
|

Whole-profile soil organic matter content, composition, and stability under cropping systems that differ in belowground inputs

Abstract: Subsoils have been identified as a potential carbon sink because they typically have low soil organic carbon (SOC) concentrations and high SOC stability. One proposed strategy to increase SOC stocks is to enhance C inputs to the subsoil by increasing crop rotation diversity with deep-rooted perennial crops. Using three long-term field trials in Iowa (study durations of 60, 35, and 12 years), we examined the effects of contrasting cropping systems [maize (Zea mays L.)-soybean (Glycine max (L.) Merr) (= two-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…This shows the impact that the areas of SC, PP, and NTS caused on the quantity and quality of C in the most superficial layers of the soil, compared with the NF area. Similar results were observed by other authors in several study areas (Rosset et al, 2019;Lavallee et al, 2020;Poffenbarger et al, 2020).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This shows the impact that the areas of SC, PP, and NTS caused on the quantity and quality of C in the most superficial layers of the soil, compared with the NF area. Similar results were observed by other authors in several study areas (Rosset et al, 2019;Lavallee et al, 2020;Poffenbarger et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…Among the many attributes analyzed to evaluate the effects of the management systems and soil quality (SQ), soil organic matter (SOM) stands out (Nanzer et al, 2019;Lavallee et al, 2020;Poffenbarger et al, 2020). Thus, one of the methods for evaluating SQ is the analysis of C compartments of the physical fractions of the SOM (Cambardella and Elliott, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Persson, Bergkvist, and Kätterer (2008) found that 2‐year ley periods in a 6‐year crop rotation could at most slow the decrease in topsoil SOC stocks over a 31‐year period in Sweden. In a recent long‐term field study, Poffenbarger et al (2020) also reported minor effects of cropping systems on SOC stocks. Bolinder, Kätterer, Andrén, and Parent (2012), however, found a stronger beneficial effect of forage‐based rotation on SOC stock, most likely due to decreased tillage intensity and slight higher carbon input to the soils in comparison to the rotation with annual crops only.…”
Section: Discussionmentioning
confidence: 93%
“…Global soil carbon (C) stocks are about three times greater than atmospheric C stocks (Jackson et al., 2017), so slight changes in soil organic C (SOC) stocks will impact global climate (Fargione et al., 2018; Lal, 2010; Rustad, Huntington, & Boone, 2000; Stockmann et al., 2013). Agricultural soils are a significant part of the overall reduction strategy, so investigations into the accumulation and stabilization of SOC in agricultural systems have increased considerably in recent years (Poffenbarger et al., 2020; Smith et al., 2020; Zomer, Bossio, Sommer, & Verchot, 2017). In the policy realm, the 4 per 1,000 Initiative calls for an annual increase in SOC stocks of 0.4% on agricultural lands globally to reduce the CO 2 concentration in the atmosphere (COP21, 2015; Rumpel, Lehmann, & Chabbi, 2018).…”
Section: Introductionmentioning
confidence: 99%